Commitment vs. Flexibility - Amador, Manuel; Werning, Ivan; Angeletos, George-Marios (Econometrica, 2006)
We study the optimal trade-off between commitment and flexibility in a consump- tion-savings model. Individuals expect to receive relevant information regarding tastes and thus they value the flexibility provided by larger choice sets. On the other hand, they also expect to suffer from temptation, with or without self-control, and thus they value the commitment afforded by smaller choice sets. The optimal commitment problem we study is to find the best subset of the individual's budget set. This problem leads to a principal-agent formulation. We find that imposing a minimum level of savings is always a feature of the solution. Necessary and sufficient conditions are derived for minimum-savings policies to completely characterize the solution. We also discuss other applications, such as the design of fiscal constitutions, the problem faced by a paternalist, and externalities. Copyright The Econometric Society 2006.